Exploration of Pragmatic Strategies in a 3-Year-Old Child: A Psycholinguistic Perspective from Daily Interactions - Jefriyanto Saud; Zainal Rafli; Fathiaty Murtadho (LPPM Institut Pendidikan Nusantara Global, 2025)
This study employs a qualitative descriptive case‑study approach grounded in participatory observation of daily interactions, taped dialogue transcripts, and semi-structured parent interviews to analyze the pragmatic techniques of Zalva, a three-year-old child, through the lenses of Dardjowidjojo and Dworetzsky. By systematically coding and thematically analyzing naturalistic data, the research reveals that Zalva demonstrates sophisticated strategies such as giving advice, shifting topics, and offering reflective responses to social conventions. For instance, she counsels her father to refrain from consuming cold drinks and adeptly counters indirect criticism by asserting, “Zalva is occupied, please do not interrupt me.” These findings align with Dardjowidjojo’s emphasis on social and cultural interaction and Dworetzsky’s focus on cognitive adaptation in context. Practically, parents are encouraged to model directive and reflective speech acts during routine exchanges, while early‑childhood educators can incorporate role‑play and guided dialogue activities to foster children’s pragmatic competence. Future research should extend this case‑study framework to diverse cultural settings to deepen our understanding of early pragmatic development and its applications in educational and caregiving contexts.